Dynamic interactions of research, publication, researchers, institutions, and countries: A Quintuple Helix model perspective on research impact - Mudassar Arsalan,; Omar Mubin,; Abdullah Al Mahmud, (Malaysian Journal of Library and Information Science, 2024)
This review paper introduces and explores the Research Impact Quintuple Helix Model, a comprehensive framework designed to analyse and enhance the impact of research across societal, economic, and environmental dimensions. Unlike traditional models focusing on sectoral collaboration for innovation and economic development, this model integrates five critical elements - Research, Publication, Researchers, Institutions, and Countries - offering a holistic approach to understanding research impact. The study systematically examines the dynamic interactions among these elements, emphasising their collective role in fostering collaborative synergies, interdisciplinary research, and effective resource allocation. By aligning research activities with broader societal needs and environmental considerations, the model aims to extend the scope of research impact beyond academic achievements, highlighting the importance of policy alignment, societal engagement, and sustainable practices. Key comparisons with the standard Helix models demonstrate the unique contributions of the research impact quintuple helix model, illustrating its potential to address specific challenges in maximising research benefits. The paper identifies strategic collaborations and policy implications that could significantly enhance the societal benefits of research, advocating for a structured integration of the model’s elements into research and policy-making processes. The review concludes by recognising limitations in the existing literature and calling for empirical studies to validate and refine the model. Future research should incorporate quantitative methods to measure the impact effectively, aiming to transform theoretical insights into actionable strategies for a sustainable and impactful research ecosystem.